ECONOMIC ASSESSMENT OF INTEGRATED FARMING LIVESTOCK CROPS WITH GOAT ON DRY LAND IN THE DISTRICT SUMBAWA - Handoko, Broto; ., Ibrahim; ., Suhaema (Jurnal Lembaga Penelitian Universitas Mataram, 2014)
This study aims to: 1) determine the costs and revenues in the integrated farming on dry land, 2) determine the feasibility of integrated farming on dry land, and 3) know the constraints faced by farmers in integrated farming activities on dry land. The results showed that the integrated farming activities on dry land farming consists of 3 pattern is a pattern of 1 (rice, green beans and goats), pattern 2 (rice and goats) and pattern 3 (rice, corn and goats) so that the cost used in integrated farming on dry land for the first pattern of Rp. 14.146.639, 2 patterns of Rp. 8.134.319 and Rp 3 pattern. 16.230.362. Income pattern of Rp. 18.283.465, 2 patterns of Rp. 14.228.181 and Rp 3 pattern. 20.974.835. Integrated farming viable on dry land to be developed for the R/C >1 and BEP acceptance, production and greater production rates of acceptance BEP, BEP production and prices. Constraints faced by farmers is erratic rainfall, high labor costs and capital interest and diarrheal disease in goats.